Teaching agrobiodiversity: a curriculum guide for higher education - Rudebjer, P.G.; Schagen, Boudy van; Chakeredza, Sebastian; Njoroge K; Kamau H; Baena, M. (Bioversity International, 2011)
In recent years, research has yielded a rapidly growing knowledge base on how agricultural biodiversity is linked to food security, nutrition, livelihoods, environmental sustainability and climate change. It is now urgent to inform higher agricultural education systems accordingly, with a view to integrating such knowledge into curricula. At present, agrobiodiversity courses or programmes are rare or non-existent, according to regional consultations with universities in 2009 and 2010.